Song of Susannah - King, Stephen, 1947-; Anderson, Darrel (Hampton Falls, N.H. : Donald M. Grant ; New York : Distributed by Simon & Schuster, 2004)
While Jake, Father Callahan, and Oy struggle to free Susannah Dean, whose body is possessed by a demon-mother named Mia, Roland and Eddie find themselves swept by magic to East Stoneham, Maine, in the summer of 1977.
840
Accelerated Reader AR
Maine author. Stephen King was born in Portland, attended Durham Elementary School and Lisbon High, and was graduated from the University of Maine-Orono with a degree in English in 1970. He lives in Bangor, Me. and Florida.
Keywords: Roland (Fictitious character : King) -- Fiction; Horror tales; New York (N.Y.) -- Fiction; Maine -- Fiction; Fantasy fiction